Carbon Capture: Storage vs. Utilization - Michel Moreaux; Jean-Pierre Amigues; Gerard van der Meijden; Cees Withagen (Tinbergen Institute, 2022)
Carbon capture and storage (CCS) seems an appealing option to meet the ambitious objectives of the Paris Agreement. Captured carbon emissions can also be injected in active fields to enhance recovery: Carbon capture and utilization (CCU). We study a dynamic model of CCS and CCU of an economy subject to a carbon budget. We demonstrate that if the social planner implements CCU, it does so at the beginning of the planning period and stops before the budget has been depleted. On the contrary, if CCS occurs in the social optimum, this happens only once the carbon budget has been depleted. We show that the relationship between the carbon budget and the carbon price can be non-monotonic if CCU occurs. Our model features three state variables: The stock of fossil fuel, the stock of atmospheric carbon and the stock of injected carbon in active fields. We derive frontiers that separate regions in initial-stock-space with and without CCS and CCU regimes in the social optimum. Finally, we compare the social optimum with the decentralized market outcome.
Keywords: Q54; Q30; Q35; Q42; 330; global warming; carbon capture and storage; enhanced recovery; non-renewable resources; renewable resources